The Jewish Cronenberg: a cinema of therapeutic disintegration*. Issue 2 (3rd April 2017) - Lowenstein, Adam
Abstract: This essay examines David Cronenberg's Scanners (1981) alongside Maps to the Stars (2014) to argue that we should resist the impulse to which many critics succumb when faced with Cronenberg's bewilderingly heterogeneous body of work: dividing his career into distinct periods, usually separated by genre labels. Instead, we need to recognize the formal and thematic discourse that has characterized his cinema from the beginnings to the present: the need for a therapy that works alongside the impossibility of ever fulfilling that need. Whether within the films as narrative and audiovisual structures or across the films as a continuing dialog with his audience as his work metamorphoses, Cronenberg's cinema constantly reaches toward therapy as a solution to the schisms that shatter ties between mind and body, only to disintegrate the possibility that therapy can heal such schisms. But the cycle of activating and then disintegrating the therapeutic impulse is itself an illumination of how we imagine therapy as a bridge between the personal and the social, the self and the other, the brain and the flesh. I contend that a vital context for Cronenbergian therapy is Jewish-inflected philosophical thought, especially through the figures of Siegfried Kracauer, Emmanuel Levinas, and Franz Rosenzweig.